2023
DOI: 10.3389/fcimb.2023.1234994
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the virulence and inflammatory response of Staphylococcus aureus strains isolated from diabetic foot ulcers

Abstract: Staphylococcus aureus strains isolated from diabetic foot ulcers (DFUs) have less virulence, but still cause severe infections. Furthermore, hypovirulent S. aureus strains appear to be localized in the deep tissues of diabetic foot osteomyelitis, indicating that the unique environment within DFUs affects the pathogenicity of S. aureus. In this study, the cell-free culture medium (CFCM) of S. aureus strains isolated from DFUs exhibited higher cytotoxicity to human erythrocytes than those isolated from non-diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…They showed that a particular combination of virulence genes ( cap8 , sea , sei , lukE , and hlgv ) was statistically correlated with infection and may serve as a prediction factor for the wound status at the follow-up ( Sotto et al, 2008 ). Moreover, Wu et al (2023) demonstrated that the levels of glucose and its metabolites impact on the virulence and inflammatory response of S. aureus strains isolated from diabetic foot ulcers. Regarding chronic venous ulcers, Cwajda-Białasik et al, (2021) proved that culture-positive lesions, and, therefore, colonization or infection status, are more frequent in older patients (age > 65 years) with chronic and larger wounds (ulcer duration > 12 months, ulceration area > 8.25 cm 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that a particular combination of virulence genes ( cap8 , sea , sei , lukE , and hlgv ) was statistically correlated with infection and may serve as a prediction factor for the wound status at the follow-up ( Sotto et al, 2008 ). Moreover, Wu et al (2023) demonstrated that the levels of glucose and its metabolites impact on the virulence and inflammatory response of S. aureus strains isolated from diabetic foot ulcers. Regarding chronic venous ulcers, Cwajda-Białasik et al, (2021) proved that culture-positive lesions, and, therefore, colonization or infection status, are more frequent in older patients (age > 65 years) with chronic and larger wounds (ulcer duration > 12 months, ulceration area > 8.25 cm 2 ).…”
Section: Introductionmentioning
confidence: 99%